Le Fragment et le Hérisson. - Semin, Didier (Les Sables d'Olonne : Musée de l'Abbaye Sainte-Croix, 1986)
Kupka, Franz ; Ray, Man ; Brauner, Victor ; Paik, Nam June ; Kosuth, Joseph ; Anselmo, Giovanni ; Lavier, Bertrand ; Fleischer, Alain ; Vilmouth, Jean-Luc ; Tosani, Patrick
Le Fragment et le Hérisson, Musée de l'Abbaye Sainte-Croix, Les Sables d'Olonne, novembre - décembre 1986
boek